The role of the microbiome in the development, progression and treatment of cancer : El papel del microbioma en el desarrollo, progresión y tratamiento del cáncer - Callapiña De Paz, Mariana (2024)
It is known that there is a great variety of extensive and diverse populations of bacteria, viruses and fungi occupying every surface of the body. It is estimated that there are almost 30 trillion bacterial cells living inside each human being, and there is a 100 times higher genetic diversity of bacteria, which encodes metabolic capabilities that influence their microbial ecosystem and the tissue-specific immune system of the organism. Guest. These microbes are known collectively as the human microbiota, while the set of microorganisms, genes and metabolites that inhabit a certain place are known as the microbiome.